The Evidence for Brain Injury in Whiplash Injuries - Michael P. Alexander (Pain Research and Management)
The evidence that brain damage can occur in injuries that produce whiplash is reviewed. The clinical phenomena for the two injuries are the same. Pure whiplash injury implies no, or minimal head contact, but many patients also have head contact against a head rest or the steering wheel or windshield. The relative severity of the neck injury and the head injury distinguishes whiplash from mild closed head injury. If there is brain injury is some patients with whiplash, it, by definition, falls at the mildest end of the concussion spectrum. The relationship between these two injuries is examined.